Transforming the purchasing strategy of high-tech medical equipment in healthcare systems. Issue 3 (1st October 2016) - Knight, Amy; Blessner, Paul; Olson, Bill
ABSTRACT: In healthcare settings, implementing centralized strategic sourcing in healthcare systems can result in stronger supply chains, improved logistics, and improve the treatment of patients who utilize the newly purchased technologies. This study examines health technology acquisition and purchasing literature and develops a cross-functional acquisition strategy that leverages the acquisition of high-tech medical equipment for healthcare systems. The strategy is derived by combining best practices developed using decentralized purchasing strategies by healthcare facilities and successful buyer-supplier relationships from multiple industries. The strategy allows hospital systems to evaluate the efficacy of the equipment, the ability of the equipment to benefit the patient population, and the ability of the equipment to integrate with existing hospital IT systems. If the equipment proves to be a beneficial acquisition, the system can then form a buyer-supplier relationship to allow for the most efficient acquisition and installation of the equipment in multiple facilities, in a manner that also ensures the greatest usage of the new equipment by medical center staff.